The Pleiotropic Immunomodulatory Functions of IL-33 and Its Implications in Tumor Immunity - Afferni, Claudia; Buccione, Carla; Andreone, Sara; Galdiero, Maria Rosaria; Varricchi, Gilda; Marone, Gianni; Mattei, Fabrizio; Schiavoni, Giovanna (Frontiers in Immunology, 2018)
Interleukin-33 (IL-33) is a IL-1 family member of cytokines exerting pleiotropic activities. In the steady-state, IL-33 is expressed in the nucleus of epithelial, endothelial and fibroblast-like cells acting as a nuclear protein. In response to tissue damage, infections or necrosis IL-33 is released in the extracellular space, where it functions as an alarmin for the immune system. Its specific receptor ST2 is expressed by a variety of immune cell types, resulting in the stimulation of a wide range of immune reactions. Recent evidences suggest that different IL-33 isoforms exist, in virtue of proteolitic cleavage or alternative mRNA splicing, with potentially different biological activity and functions. Although initially studied in the context of allergy, infection and inflammation, over the past decade IL-33 has gained much attention in cancer immunology. Increasing evidences indicate that IL-33 may have opposing functions, promoting or dampening tumor immunity, depending on the tumor type, site of expression and local concentration. In this review we will cover the biological functions of IL-33 on various immune cell subsets (e.g., T cells, NK, Treg cells, ILC2, eosinophils, neutrophils, basophils, mast cells, DCs, and macrophages) that affect anti-tumor immune responses in experimental and clinical cancers. We will also discuss the possible implications of diverse IL-33 mutations and isoforms in the anti-tumor activity of the cytokine and as possible clinical biomarkers.